Counseling Hypertension and Giving “Seru Gasipala Juice” In Elderly Women on Gandul Neighborhood 02 Cinere Village, Depok - Siauta, Jenny Anna; Reksaningtyas , Astri; Aryanti , Pivi Dewi; Ruandayadi, Nadiya; Mujayanti, Rini; Wahyuni, Yuyun; Tyastuti, Dyah Purwaning (International Journal of Community Services, 2023)
Background: In the target area in Gandul Village, there were 59 elderly women for the January–March 2023 period; 81.4% of hypertensive elderly women, and 66% did not routine check their health conditions at the nearest health service. Objective: Diagram the formulation of problems or needs based on the priority of problems related to non-communicable diseases and women's health throughout their life cycle together with the community. Methodology: The data taken was secondary data that we got from Cinere Health Centre. The method for prioritizing problems used the ultrasound method. So we determined problem of hypertension in elderly women was the main problem that occurs in Gandul Village area at this community station. Results: It was found that 81.4% of elderly women suffered from hypertension between January and March 2023. Therefore, the group intervened in the form of counseling on hypertension and providing nutrition for Seru Gasipala Juice (celery, orange, and papaya juice), which can help reduce high blood pressure in elderly women. Conclusion: Counseling on "Increasing the Knowledge of Elderly Women about Hypertension by Giving Celery, Orange, and Papaya Juice in Gandul Village" can help reduce and prevent high blood pressure. Increased knowledge and skills for health counseling participants about juicing with the lecture method. The empowerment of midwives and cadres in blood pressure monitoring expected to be well realized by giving several examples of how to give celery, orange, and papaya juice.